Net pancake maker / Muhammad Fakhrun Amin Yahaya, Muhammad Firdaus Amin Mohd Zainee and Nur Syuhada Mohd Yusof - Yahaya, Muhammad Fakhrun Amin; Mohd Zainee, Muhammad Firdaus Amin; Mohd Yusof, Nur Syuhada (2016)
Net Pancake Maker is high voltage device. The main function of this device is to make the net pancake automatically. To be specific, when the device started with ON the power supply and the temperature sensor start operating. The temperature sensor will detect the temperature of pan. The automatic valve were set to 2 minutes before the valve open to release the net pancake batter. Shape the pancake with our own creativity manually. The valve will close after it reach the end of the time.